2022
DOI: 10.3390/jof9010015
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Responses of Ectomycorrhizal Fungus, Cenococcum geophilum, to Drought Stress

Abstract: With global warming, drought has become one of the major environmental pressures that threaten the development of global agricultural and forestry production. Cenococcum geophilum (C. geophilum) is one of the most common ectomycorrhizal fungi in nature, which can form mycorrhiza with a large variety of host trees of more than 200 tree species from 40 genera of both angiosperms and gymnosperms. In this study, six C. geophilum strains with different drought tolerance were selected to analyze their molecular resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…The inoculation of C. geophilum in Masson pine seedlings resulted in enhanced plant growth and stress resistance through improved biomass production, photosynthesis, and nutrient status [41]. Our previous research confirmed that C. geophilum exhibited resistance to drought, high temperature, and heavy metal stress by increasing nutrient absorption and antioxidant enzyme activity and upregulating genes encoding antioxidant enzyme activity, ubiquinone, and other terpenoid quinones and metabolism of compounds [42][43][44]. Additionally, our research demonstrated that the inoculation of C. geophilum effectively alleviated heavy metal-induced toxicity in Pinus massoniana seedlings [45].…”
Section: Discussionmentioning
confidence: 63%
“…The inoculation of C. geophilum in Masson pine seedlings resulted in enhanced plant growth and stress resistance through improved biomass production, photosynthesis, and nutrient status [41]. Our previous research confirmed that C. geophilum exhibited resistance to drought, high temperature, and heavy metal stress by increasing nutrient absorption and antioxidant enzyme activity and upregulating genes encoding antioxidant enzyme activity, ubiquinone, and other terpenoid quinones and metabolism of compounds [42][43][44]. Additionally, our research demonstrated that the inoculation of C. geophilum effectively alleviated heavy metal-induced toxicity in Pinus massoniana seedlings [45].…”
Section: Discussionmentioning
confidence: 63%
“…Cenococcum geophilum, characterized by abundant genetic diversity, holds ecological significance linked to its genetic variations [21]. Numerous studies have highlighted the varying resistance levels of different ecotypic strains of C. geophilum to stresses such as drought, high temperature, heavy metals, and salt [23,[37][38][39]. Nevertheless, existing studies primarily focus on the strain's inherent stress resistance mechanism, with limited exploration of the symbiotic relationship between strains and plants in facing diverse stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Coleman et al [22] has illuminated its role in preserving cellular integrity under conditions of water deficit while mitigating the surge in reactive oxygen species (ROS) typically observed during drought stress. Furthermore, recent findings by Li et al [23] underscore the ability of different ecotypes of C. geophilum to induce the expression of drought-related genes when subjected to drought conditions, thereby enhancing drought resistance. It is important to note that different ecotypes of C. geophilum exhibit distinct responses to drought, presenting an intriguing avenue for further exploration in this context.…”
Section: Introductionmentioning
confidence: 98%
“…The survival of C. geophilum in the Arctic further supports this observation (Miyamoto et al, 2022 ). Additionally, C. geophilum can thrive even under relatively arid conditions, potentially due to its ability to regulate osmotic pressure, and enhance antioxidant enzyme activity and alleviate drought stress (Li, Yuan, et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%